Absence of venous thromboembolism risk following quadrivalent human papillomavirus vaccination, Vaccine Safety Datalink, 2008–2011. Issue 1 (2nd January 2016) - Naleway, Allison L.; Crane, Brad; Smith, Ning; Daley, Matthew F.; Donahue, James; Gee, Julianne; Greene, Sharon K.; Harrington, Theresa; Jackson, Lisa A.; Klein, Nicola P.; Tseng, Hung Fu; Vellozzi, Claudia; et al.
Highlights: The risk of VTE in the 1–60 days after HPV4 exposure was calculated in the VSD. Using diagnosis codes and medical record review, 156 confirmed cases were identified. Nearly all (97%) cases had at least one known VTE risk factor. Sixteen (10%) confirmed cases occurred in the 1–60 days following HPV4 exposure. No elevation in VTE risk following HPV4 exposure was observed. Abstract: Background: To investigate concerns about a potential association between quadrivalent human papillomavirus vaccination (HPV4) and venous thromboembolism (VTE), we conducted a self-controlled case series study in adolescents and young adults 9–26 years of age in the Vaccine Safety Datalink. Methods: We identified potential VTE cases diagnosed in 2008 through 2011 who had also received at least one HPV4 dose during that period. We confirmed each presumptive diagnosis by medical record review. We calculated incidence rate ratios (IRRs) and 95% confidence intervals (CI) to estimate the risk in the 1–60 day period following HPV4 exposure and in subsets of that period. IRRs were stratified by age, gender, hormonal contraceptive use, and recent surgery or trauma. Results: We identified 313 potential cases of VTE among HPV4 vaccinees, and 291 (93%) had sufficient medical records for review. Of these, we confirmed 156 (54%) cases. VTE was uncommon among males ( n  = 3) and 9–12 year olds ( n  = 4). Nearly all confirmed cases (97%) had at least one known risk factor for VTE, including hormonal contraceptive use, obesity, and hypercoagulability. Sixteen (10%) confirmed cases occurred in the 1–60 days following HPV4 exposure. The risk of VTE varied from 1.47 (95% CI: 0.47–4.64) in the 1–7 days following HPV4 exposure to 0.92 (95% CI: 0.54–1.57) in the 1–60 days following vaccination. It was not possible to calculate a stratified IRR for males due to small sample size; the other risk factors evaluated did not significantly affect the risk of VTE after HPV4 exposure. Conclusion: The risk of developing VTE among 9- to 26-year-olds was not elevated following HPV4 exposure. Sample size limited our ability to rigorously evaluate potential effect modifiers, such as gender, through stratified analysis.